Soothsaying DOM: A Current Perspective on the Future of Oceanic Dissolved Organic Carbon - Wagner, Sasha; Schubotz, Florence; Kaiser, Karl; Hallmann, Christian; Waska, Hannelore; Rossel, Pamela E.; Hansman, Roberta; Elvert, Marcus; Middelburg, Jack J.; Engel, Anja; Blattmann, Thomas M.; Catalá, Teresa S.; et al. (Frontiers in Marine Science, 2020)
The vast majority of freshly produced oceanic dissolved organic carbon (DOC) is derived from marine phytoplankton, then rapidly recycled by heterotrophic microbes. A small fraction of this DOC survives long enough to be routed to the interior ocean, which houses the largest and oldest DOC reservoir. DOC reactivity depends upon its intrinsic chemical composition and extrinsic environmental conditions. Therefore, recalcitrance is an emergent property of DOC that is analytically difficult to constrain. New isotopic techniques that track the flow of carbon through individual organic molecules show promise in unveiling specific biosynthetic or degradation pathways that control the metabolic turnover of DOC and its accumulation in the deep ocean. However, a multivariate approach is required to constrain current carbon fluxes so that we may better predict how the cycling of oceanic DOC will be altered with continued climate change. Ocean warming, acidification, and oxygen depletion may upset the balance between the primary production and heterotrophic reworking of DOC, thus modifying the amount and/or composition of recalcitrant DOC. Climate change and anthropogenic activities may enhance mobilization of terrestrial DOC and/or stimulate DOC production in coastal waters, but it is unclear how this would affect the flux of DOC to the open ocean. Here, we assess current knowledge on the oceanic DOC cycle and identify research gaps that must be addressed to successfully implement its use in global scale carbon models.